Use of optical coherence tomography for the diagnosis of preclinical lesions of circumscribed palmar hypokeratosis. (4th January 2017) - Abignano, G.; Kapadia, A.; Lettieri, G.; Goodfield, M.; Emery, P.; McGonagle, D.; Del Galdo, F.; Mikeljevic, J.
Summary: Circumscribed hypokeratosis of palms and soles is a rare dermatosis, usually affecting women. Diagnosis is mainly based on the clinical characteristics, including the clinical appearance and anatomical site of the skin lesions and on the demographic features of the affected patients, usually middle‐aged to elderly women. Skin biopsy may be performed to confirm clinical diagnosis. Optical coherence tomography (OCT) is a technique that has been undergone substantial development in dermatology in recent years, and its use in clinical practice has been growing progressively. Several dermatological conditions have been studied with this tool, but to our knowledge, it has not been used to investigate this form of hypokeratosis. We report a case of circumscribed palmar hypokeratosis for which diagnosis was confirmed by OCT, which was performed as the patient was reluctant to undergo skin biopsy because of its invasiveness. We highlight the potential use of OCT in obtaining a virtual skin biopsy to confirm clinical diagnosis and identify preclinical skin lesions amenable to early treatment.